If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -8 = 9x + 7 + -8x Combine like terms: -6 + -8 = -14 -14 = 9x + 7 + -8x Reorder the terms: -14 = 7 + 9x + -8x Combine like terms: 9x + -8x = 1x -14 = 7 + 1x Solving -14 = 7 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -14 + -1x = 7 + 1x + -1x Combine like terms: 1x + -1x = 0 -14 + -1x = 7 + 0 -14 + -1x = 7 Add '14' to each side of the equation. -14 + 14 + -1x = 7 + 14 Combine like terms: -14 + 14 = 0 0 + -1x = 7 + 14 -1x = 7 + 14 Combine like terms: 7 + 14 = 21 -1x = 21 Divide each side by '-1'. x = -21 Simplifying x = -21
| -x^2-23x-60=0 | | 17/19+1/19 | | w/4=13 | | -3+21=m-8 | | x*2-0.2x*4x-2400=0 | | 4x-8=5x-2(x+2) | | f(1.8)=2x*x-16x+63 | | x/x+4 | | 1/x+4 | | x-4/x-16 | | f(1.8)=2x*2x-16x+63 | | y/8=17 | | (x-9)(2x^2+x-3)= | | 5/12+1/2 | | 9y-12y=-10-14 | | .24y-4=.14y+2-.7y | | 1/15+3/5 | | 2/5+9/20 | | 8x-4=-29+3x | | x^4+81=18x^2 | | 8t+(3t-4t)= | | 9n-3y=-3 | | -11r-(5-6r)=-(6-3r)+1 | | 3x-7y=-15 | | 13/4(3x+3/4) | | 8(3x+2)/5=x+3 | | 3x-2x+6-1=4x+2 | | 2n-4y=-24 | | 4(y-2)/5=-2y | | 6x(2x-1)=9x+2(2-x) | | 6(x+3)/4=3x-2 | | -34(12-8)=-8 |